Readiness of General Education Teachers for Implementation of Universal Design for Learning in General Education Classrooms for Differently able Students - Faiza Jaleel، Abid Hussain Ch, Asma Kanwal (JIE, 2022)
This descriptive study was aimed to investigate “readiness ofgeneral education teachers for implementation of universal design for learning in general education classrooms for students with disabilities”. Main objective of the study was to investigate the readiness of prospective and in-service general education teachers for implementation of universal design for learning in general education classrooms for students with disabilities. The population of the study was prospective and in-service general education teachers from which a sample of 200 (80 in service and 120 prospective) was recruited by purposive sampling technique from various educational institutions in Lahore. A validated five-point rating scale comprised of 28 questions was constructed (α=0.939).